Environmental reverberation affects processing of sound intensity in right temporal cortex. Issue 8 (22nd July 2013) - Altmann, Christian F.; Ono, Kentaro; Callan, Akiko; Matsuhashi, Masao; Mima, Tatsuya; Fukuyama, Hidenao
Abstract Although sound reverberation is considered a nuisance variable in most studies investigating auditory processing, it can serve as a cue for loudness constancy, a phenomenon describing constant loudness perception in spite of changing sound source distance. In this study, we manipulated room reverberation characteristics to test their effect on psychophysical loudness constancy and we tested with magnetoencephalography on human subjects for neural responses reflecting loudness constancy. Psychophysically, we found that loudness constancy was present in strong, but not weak, reverberation conditions. In contrast, the dependence of sound distance judgment on actual distance was similar across conditions. We observed brain activity reflecting behavioral loudness constancy, i.e. inverse scaling of the evoked magnetic fields with distance for weak reverberation but constant responses across distance for strong reverberation from ~210 to 270 ms after stimulus onset. Distributed magnetoencephalography source reconstruction revealed underlying neural generators within the right middle temporal and right inferior anterior temporal lobe. Our data suggest a dissociation of loudness constancy and distance perception, implying a direct usage of reverberation cues for constructing constant loudness across distance. Furthermore, our magnetoencephalography data suggest involvement of auditory association areas in the right middle and right inferior anterior temporal cortex in this process.